Manajemen Pembelajaran Pendidikan Agama Islam Pada Sekolah Luar Biasa Negeri dan Sekolah Luar Biasa YPAC Surakarta - Sapto Hendro Sutejo (Journal on Education, 2023)
Islamic Religious Education learning management can also be interpreted as a management process including planning, organizing, controlling and evaluating activities related to the learning process by including various factors in it to achieve goals. In accordance with the above process, the aim of this research is to describe and analyze teachers' abilities in planning, organizing, implementing and evaluating learning management in Islamic Religious Education at State Special Schools and Special Schools at the Surakarta Disabled Children's Education Foundation. Thus, this research uses a qualitative descriptive approach, with a case study type design. Data collection techniques were carried out in three ways, namely: Observation, interviews and documentation. Then the data was analyzed in two stages, namely: individual case data analysis and cross-case data analysis. Meanwhile, the data sources in this research are: Principal, Deputy Principal, Teachers, employees and students. The results of this research show that first, the basis of religious behavior is developed in State Special Schools and Special Schools of the Surakarta Disabled Children's Education Foundation by practicing religious values that are believed and carried out in daily life, and utilizing additional hours in extracurricular activities. Second, the design of implementing Islamic Religious Education Learning management which is very unique, such as implementing religious behavior at the Surakarta State Special School, through 3.S behavior (smile, greet, say hello) and the behavior of greeting, excuse me, sorry and thank you, and read thoroughly. writing the Qur'an, midday prayers, spiritual prayers, noon prayer in congregation, and group prayers, commemoration of Islamic holidays, imtaq activities and reading the Qur'an, group prayers at the beginning and end of lessons, shaking hands between school members, wearing clothing Muslims. Third, the Surakarta Disabled Children's Education Foundation Special School, has religious activities for major Islamic commemorations, the art of reading the Koran, lectures on religion, reading the Koran, the practice of midday prayers in congregation, sacrifices during Idhul Adha, fast Islamic boarding schools in the month of Ramadhan and others. There is something that is quite unique in both schools, namely a consistent attitude in building a mindset, especially at the Surakarta Disabled Children's Education Foundation Special School. As soon as they enter this school, the students' mindset has been built towards behavior 5. S (smile, greet, greet, be polite and courteous).